(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
China is one of the major neighboring states with the longest border with Central Asia. This region plays an important role in China’s “One Belt, One Road” initiative. The fact that China directly borders three Central Asian countries increases its constant interest in the region. From this perspective, over the past 20 years, China’s investments in various directions in Central Asia have been met with great attention. Indeed, China’s direct border with Kazakhstan, Kyrgyzstan, and Tajikistan has led to active cooperation trends with these countries in every sphere, and its influence remains strong to this day. Moreover, Uzbekistan, located in the center of Central Asia and not sharing a border with China, has China as its main partner in the economic sphere. This is clearly demonstrated in current statistics, where China has become the leading investor in Uzbekistan’s industry, ranking first among import partners and achieving the highest indicators in exports. In addition, Turkmenistan—another state without a direct border with China—also maintains mutually beneficial trade relations with Beijing. From this perspective, China’s policy toward Central Asia may be considered more promising and relevant compared to other major power centers. This article highlights China’s “soft power” approaches in Central Asia based on SWOT analysis.